The process of 21st-century English learning at an international primary school in Cirebon - Ika Maratus Sholikha; Farouk Imam Arrasyid; Wakhid Nashruddin (Universitas Sarjanawiyata Tamansiswa, 2022)
In the 21st century of the fourth industrial revolution, global access and disruptive technology need to develop learners to acquire 21st-century skills that rely on communications, collaboration, creativity, critical thinking teaching strategy, learning process, classroom management, and assessment of paramount importance. The content analysis used the qualitative narrative. The findings allowed students to survive and function with the rapidly evolved, global, and complex world, whilst teachers and other education practitioners were suggested to reform and reconsider the instructional practices including, among others learning materials used in the classroom that aligned with the current situation by involving 2 English teachers and 17 students. Hence, this study investigated characteristics of the 21st-century for EFL Learning, the strategies used by English teachers in teaching English, and the process of students learning in the 21st century at the international level.